1994
DOI: 10.1016/0014-5793(94)80288-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of α2‐macroglobulin receptor/low density lipoprotein receptor‐related protein is increased in reactive and neoplastic glial cells

Abstract: a,-Macroglobuhn receptor/low density hpoprotem receptor-related protein (cc,M-RILRP) IS a multi-functional cell-surface receptor that has been tmphcated m diverse physiologic processes In normal human brain, a,M-R/LRP IS expressed prmclpally by pyramldal neurons with locahzation to cell bodies and proximal processes By contrast, a,M-R/LRP 1s not present m either the cell bodies or processes of most normal macrogha (mcludmg astrocytes) In this mvestlgatlon, we studied the expression of a,M-FULRP m the brain, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
44
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 25 publications
7
44
0
1
Order By: Relevance
“…In CNS injury, LRP1 expression significantly increases in reactive astrocytes (Lopes et al, 1994). Our previous studies suggest that LRP1-dependent phagocytosis of myelin debris occurs across diverse cell types (Gaultier et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In CNS injury, LRP1 expression significantly increases in reactive astrocytes (Lopes et al, 1994). Our previous studies suggest that LRP1-dependent phagocytosis of myelin debris occurs across diverse cell types (Gaultier et al, 2009).…”
Section: Discussionmentioning
confidence: 88%
“…In the normal human brain, LRP1 is expressed by almost all neuronal populations (Wolf et al, 1992;Bu et al, 1994;Lopes et al, 1994). In CNS injury, LRP1 expression significantly increases in reactive astrocytes (Lopes et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that increased LRP1 expression correlates with high levels of invasion (19) and, conversely, silencing of LRP1 prevents the spread of malignant cells (20). In gliomas, LRP1 expression in tumors greatly exceeded that in normal brain tissues (21) and its expression was found to be correlated with tumor aggressiveness (22). The abundant expression of LRP1 mRNA suggests that it may be involved in the uptake of ApoE phospholipid discoidal particles or ApoE-enriched high-density lipoprotein in gastric cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Interferon-␥ shuts down LRP-1 expression in macrophages by regulating transcription (LaMarre et al, 1991;Hussaini et al, 1996). In the CNS, disorders associated with inflammation increase LRP-1 expression in astrocytes (Rebeck et al, 1993;Lopes et al, 1994). LRP-1 may facilitate astrocyte activation because the LRP-1 antagonist, RAP, inhibits astrocyte activation in culture (LaDu et al, 2001).…”
Section: Discussionmentioning
confidence: 99%